Examining the knowledge, attitudes and practices of domestic and international university students towards seasonal and pandemic influenza - Seale, Holly (BioMed Central, 2012)
BACKGROUND: Prior to the availability of the specific pandemic vaccine, strategies to mitigate the impact of the disease typically involved antiviral treatment and “non-pharmaceutical” community interventions. However, compliance with these strategies is linked to risk perceptions, perceived severity and perceived effectiveness of the strategies. In 2010, we undertook a study to examine the knowledge, attitudes, risk perceptions, practices and barriers towards influenza and infection control strategies amongst domestic and international university students. METHODS: A study using qualitative methods that incorporated 20 semi-structured interviews was undertaken with domestic and international undergraduate and postgraduate university students based at one university in Sydney, Australia. Participants were invited to discuss their perceptions of influenza (seasonal vs. pandemic) in terms of perceived severity and impact, and attitudes towards infection control measures including hand-washing and the use of social distancing, isolation or cough etiquette. RESULTS: While participants were generally knowledgeable about influenza transmission, they were unable to accurately define what ‘pandemic influenza’ meant. While avian flu or SARS were mistaken as examples of past pandemics, almost all participants were able to associate the recent “swine flu” situation as an example of a pandemic event. Not surprisingly, it was uncommon for participants to identify university students as being at risk of catching pandemic influenza. Amongst those interviewed, it was felt that ‘students’ were capable of fighting off any illness. The participant’s nominated hand washing as the most feasible and acceptable compared with social distancing and mask use. CONCLUSIONS: Given the high levels of interaction that occurs in a university setting, it is really important that students are informed about disease transmission and about risk of infection. It may be necessary to emphasize that pandemic influenza could pose a real threat to them, that it is important to protect oneself from infection and that infection control measures can be effective.